Performance appraisal effect on organizational performance through employee satisfaction in UAE oil and gas companies - Salem Mohamed Abdulla Alkheyli, Aisha (2025)
All of the well-known traditional tasks are carried out by the human resources department, which also incorporates contemporary HR practices through the use of information technology resources. However,the importance of the current human resource forecast's concern on hiring practices to meet the objectives of the intended company has been downplayed. In order to determine how satisfied its employees are,the HRM department must design and implement a system for measuring employee satisfaction. Employee satisfaction with the current performance review process should also be ascertained through a survey. Employee satisfaction,assessment,and organizational performance are all strongly linked. With the increased competition among the oil and gas companies in UAE,maintaining optimal organizational performance have become inevitable. Performance appraisal is one of the most significant aspects of ensuring optimal and positive organizational performance. Performance appraisal not only aid the organization to align the individual and organizational goals,support employee development and assess their performance but it also contributes in improving employee satisfaction. The present study aimed to assess the practices of performance appraisal in oil and gas companies within UAE with four objectives namely, to analyse the effect of performance appraisal on organizational performance,to examine the effect of performance appraisal on employee satisfaction,to examine the effect of employee satisfaction on organizational performance and to investigate the mediation effect of employee satisfaction in the relationship between performance appraisal and organizational performance. For this purpose,the researcher has implemented a quantitative research design to assess the cause and relationship among variables. 374 questionnaires were disbursed to collect data from the oil and gas companies in UAE. Results depicted a significant relationship between performance appraisal and organizational performance and between employee satisfaction and organizational performance. Employee satisfaction was also a significant mediator between performance appraisal and organizational performance. The present study holds greater theoretical and practical implications. This study enhances the growing body of literature regarding the concerned and studied associations among variables. Practically,the management of oil and gas companies of UAE can also gain insights regarding the way through which performance appraisal can contribute to an improved organizational outcome. Moreover,different policies can also be designed to enhance employee satisfaction.